Desempenho de genótipos de trigo associados com Herbaspirillum seropedicae em relação à fixação biológica de nitrogênio e promoção do crescimento vegetal - Neiverth, Adeline (2011)
Wheat is the most important staple food of the world. The increase in grains productivity and protein content is correlated to increase inorganic nitrogen absorption. Usually, urea is the most convenient source of N2, but, it causes the increase in crops costs beyond injuries to the environment. The BNF realized by diazotrophics bacteria is an alternative to supplement or replace the nitrogen fertilizers and promote plant growth. The objective of this study was to evaluate the performance of Brazilian wheat genotypes for PCV( plant promoter growth) and BNF by association between diazotrophic bacteria (H. seropedicae SmR1) and wheat cultivars under in vitro and greenhouse conditions. In in vitro experiment, eight wheat plantlets of 8 genotypes were tested in tubes with liquid culture medium and these were co-cultured for 7 days with 107 cells.mL-1. As control plantlets without inoculum under the same conditions were used. The experimental design was completely randomized in a 2 x 8 factorial with 3 repetitions. We analyzed the fresh mass of roots, fresh and dry weight of shoots, total nitrogen (TN) content of NH4 +, microbial counting (CFU), glutamine synthetase activity (GS), the morphology of the roots by microscopy and molecular analysis of epiphytic and endophytic bacteria recovered after co-cultivation. In the greenhouse, it was planted five wheat genotypes. The seeds were placed in pots with 4.5 kg of soil under four treatments: 1 - Control 2 - Addition of N as urea (142 kg ha-1 of N) 3 - Addition of inoculum containing H. seropedicae (106 cells.mL-1) (Hs) and 4 - Addition of inoculum containing urea + H. seropedicae (N + Hs). The experimental design was completely randomized in a factorial 5 x 4 with 5 repetitions. The fresh mass of roots, fresh and dry weight of shoots, NT, NH4 + content and GS activity were evaluated. As agronomic parameters were evaluated the whole plant mass at the end of the phenological cycle, yield per plant and weight of 100 seeds.As results in vitro, it was observed the presence of epiphytic bacteria on the roots of all genotypes and the presence of endophytic bacteria in genotypes CD 105, CD 108, CD 111, CD 117, CD 120. There was a sharp increase of root hairs in the genotypes CD 105, CD 117, CD 119 and CD120. The cultivars CD 105 and CD 120 by the presence of endophytic bacteria showed an increase of root hairs, probably it may be the most promising for a response of BNF. The levels of NH4 +, NT and GS in the roots were not decisive for in vitro plant growth promotion. The results obtained in the greenhouse showed significant interactions among parameters, although there were were not crucial for the definition of a specific genotype which answers to the interaction. However, there was a contribution to be further studied, where the CD 120 cultivar showed evidence of association with response to the bacterium and possible occurrence of the BNF. There was no negative effect of inoculation to plants. Additional studies are needed to get answers about the interactions of these genotypes with diazotrophic bacteria related to BNF and plant growth promotion